Effects of temperature on pupal and egg development of Euphranta connexa, a candidate biological control agent for invasive swallow‐worts in North America. Issue 1 (17th March 2016) - Leroux, A.M.; Gassmann, A.; Holliday, N.J.
Abstract: Vincetoxicum rossicum (Kleopow) Barbar and Vincetoxicum nigrum (L.) (Apocynaceae) are invasive perennial weeds in North America, for which Euphranta connexa (Fabricius) (Diptera: Tephritidae) is a potential biological control agent. Female E. connexa oviposit in seed pods of European Vincetoxicum species, and developing larvae consume the seeds. Mature larvae emerge and form overwintering puparia in the soil. To facilitate laboratory rearing and the synchronization of oviposition and larval activity with vulnerable stages of target and non‐target plants, we investigated the effect of temperature on survival and development of E. connexa pupae and eggs. Field‐collected pupae from Switzerland were overwintered in cool storage and in spring, and they were placed in constant‐temperature treatments from 9.4 to 35 °C. Adults emerged at temperatures from 11.8 to 27.3 °C, and there was no evidence of pupal diapause. Rates of pupal development did not differ between sexes or among collection sites at altitudes ranging from 520 to over 1 700 m above sea level. From truncated normal models of development rate response to temperature, the estimated lower temperature threshold for pupal development was 4.2 °C and development was most rapid at 25.8 °C. When newly‐laid eggs were exposed to constant temperatures from 11.8 to 30 °C, hatch occurred at all temperatures. The estimated lower temperature threshold for egg development was 9.3 °C, and the predicted temperature at which egg development was most rapid was 31.2 °C. The models of pupal development suggest that E. connexa does not complete its life cycle at the highest altitude of our collection sites and that insects collected there were the result of dispersal from lower altitudes. The models predict that the northernmost North American sites where the insect might be released for biological control of invasive Vincetoxicum species are close to the northern limit for completion of the life cycle of E. connexa .